(untitled) (Botanica Orientalis: Journal of Plant Science, 2011)
The 29 Nepalese species of the pantropical genus Begonia largely belong to 2 sections, Begonia sect. Diploclinium and Begonia sect. Platycentrum. The former comprises tuberous species which occur along the Himalayan range. They die back during the dry season and their flowering time is strongly constrained by the onset of the monsoon. The latter comprises evergreen rhizomatous species some of which extend their distribution into more aseasonal areas such as Indo-China. They have a more extended flowering period which is not strictly constrained by the monsoon. There is a gradient of Begonia species richness increasing from west to east across Nepal, in relation to the increased intensity of the monsoon in the east. Key words: Distribution modelling; geophytes; monsoon; phenology; species richness. DOI: 10.3126/botor.v7i0.4386 Botanica Orientalis - Journal of Plant Science (2010) 7: 73-78